1993
DOI: 10.1093/bja/70.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Continuous Intercostal Bupivacaine for Pain Relief After Thoracotomy

Abstract: We studied 20 patients undergoing thoracotomy, in a double-blind, placebo-controlled crossover trial of intercostal bupivacaine. Bupivacaine 0.25% was infused at 5 ml h-1 through each of two catheters placed in the intercostal space at operation. Mean (95% confidence limits) 24-h requirements for morphine from a patient-controlled analgesia device were 29 (22-37) mg during bupivacaine infusion and 44 (32-57) mg during saline infusion (P = 0.04). Patients also recorded significantly smaller visual analogue scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 7 publications
0
21
0
7
Order By: Relevance
“…Da die kontinuierliche interkostale Wundinfusion eine geringere analgetische Potenz hat [7] und zudem bei langstreckiger interkostaler Lage von Kathetern Komplikationen bis hin zur Rippenosteomyelitis drohen [8], erfolgt der thorakale Einsatz der kontinuierlichen Wundinfusionskatheter zur perineuralen Lokalanästhetikaapplikation für einen kontinuierlichen paravertebralen Interkostalnervenblock (PVB [9,10,11,12] und Vorteile hinsichtlich der analgetischen Potenz gegenüber der alleinigen Opiatgabe demonstrieren [13].…”
Section: Kontinuierliche Wundinfusion Bei Thorakotomienunclassified
See 2 more Smart Citations
“…Da die kontinuierliche interkostale Wundinfusion eine geringere analgetische Potenz hat [7] und zudem bei langstreckiger interkostaler Lage von Kathetern Komplikationen bis hin zur Rippenosteomyelitis drohen [8], erfolgt der thorakale Einsatz der kontinuierlichen Wundinfusionskatheter zur perineuralen Lokalanästhetikaapplikation für einen kontinuierlichen paravertebralen Interkostalnervenblock (PVB [9,10,11,12] und Vorteile hinsichtlich der analgetischen Potenz gegenüber der alleinigen Opiatgabe demonstrieren [13].…”
Section: Kontinuierliche Wundinfusion Bei Thorakotomienunclassified
“…Bei Thorakotomien wurde in den zuvor zitierten Studien meistens Bupivacain 0,25% [11,12,15,17,18,19,21], gefolgt von Bupivacain 0,5% [9,10,16,20] eingesetzt. Regelhaft wurde vor der Dauerinfusion von (3)5-10 ml/h bzw.…”
Section: Wahl Und Dosierung Des Verwendeten Lokalanästhetikumsunclassified
See 1 more Smart Citation
“…A systematic review of randomized trials evaluating regional techniques for acute post‐thoracotomy analgesia 1 concluded that when thoracic epidural analgesia with local anesthetics plus opioids or continuous paravertebral block with local anesthetics are not possible, or are contraindicated, intrathecal opioid or intercostal nerve block are recommended despite insufficient duration of analgesia, which requires the use of supplementary systemic analgesia. Other studies have shown that intercostal nerve blocks were associated with significantly reduced supplementary analgesic requirements when administered acutely as repeat blocks 2 and by continuous infusion, 3 but not as a single intraoperative block. Dräger et al 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Viele Autoren konnten durch die Anwendung von Intercostalblockaden eine deutliche Reduktion des Opioidverbrauches und auch signifikant erniedrigte Schmerzscores nachweisen [6,7]. Die potentielle Komplikation eines Pneumothorax erscheint hier vergleichsweise weniger bedrohlich, da nach thoraxchirurgischen Eingriffen meist eine Drainage im Pleuraspalt belassen wird.…”
Section: Intercostalblockadeunclassified